Geology and Geochronology of the Wollaston Lake Fold Belt in Northwestern Manitoba - Weber, W.; Anderson, R. K.; Clark, G. S. (Canadian Journal of Earth Sciences, 1975)
Recent studies in the northeastern extension of the Wollaston fold belt in Manitoba suggest that Aphebian metasedimentary rocks of the southern Churchill province comprise a geosynclinal facies that is conformably overlain by a platform facies. A possible period of emergence and embryonic Hudsonian tectonism separates this lower sequence from a blanket of continental deposits, which is probably of large regional extent and includes part of the Hurwitz Group in the District of Keewatin.Rubidium–strontium total-rock isochron ages have been obtained for five rock units in the Kasmere Lake area of Manitoba. The ages reveal that the metasedimentary rocks of the Wollaston fold belt are bounded to the east by an Archean complex comprising a differentiated hypersthene-bearing rock series having a minimum age of 2745 ± 124 Ma ( 87 Rb = 1.39 × 10 −11 yr −1 ) and a quartz monzonite unit having a minimum age of 2636 ± 163 Ma.Hudsonian igneous rocks are mostly syn- to post-kinematic. The age of 1855 ± 62 Ma for a quartz monzonite of batholithic dimension coincides with the ages of similar syntectonic Hudsonian intrusions in the Northwest Territories. The age of 1800 ± 60 Ma obtained from a pelitic gneiss unit is a minimum age for the Hudsonian metamorphism and dates the end of the Hudsonian orogeny in this part of the Churchill province. An age of 1941 ± 25 Ma for a granitic gneiss along the western margin of the Wollaston fold belt indicates early or pre-Hudsonian magmatic activity.